Kewenangan Dan Ruang Lingkup Otoritas Jasa Keuangan Di Bidang Perbankan - Nurasiah Harahap (Universitas Islam Sumatera Utara, 2019)
The Financial Services Authority (OJK) is a financial service supervision institution such as the Banking Industry, Capital Market, Mutual Funds, Financing Companies, Pension Funds and Insurance. OJK has become an independent institution based on the Law Number 21 Year 2011 concerning OJK, which means it is free from intervention or interference from any party. The purpose of the establishment of OJK is that all activities in the Financial Services sector are carried out regularly, fairly, transparently and accountably; able to realize a financial system that grows in a sustainable and stable manner; and able to protect the interests of consumers and society.OJK has duties and authorities in the field of micropudential, which includes regulation and supervision of bank institutions, bank health, prudential aspects of banks, and bank checks. Whereas in the micropudential field, OJK's role is to assist Bank Indonesia (BI) to make moral appeals to the Banking Industry. Keywords: Financial Services Authority, Banking